Liver alveolar hydatid cyst diagnosed patient with right intrahepatic biliary tract obstruction: A case report with special emphasis on radiological features - Ateş, Fatih; Kara, Turgay; Şara, Halil İbrahim and Çoban, Muhammed Sami and Durmaz, Mehmet Sedat and Durmaz, Funda Gökgöz (Journal of Surgery and Medicine, 2019)
Hepatic alveolar echinococcosis is a rare parasitic disease caused by Echinococcosis multilocularis. The disease is diagnosed by a combination of serological tests, radiological modalities and histology of needle biopsy specimens. In this case, we present magnetic resonance imaging (MRI) and magnetic resonance cholangiopancreatography (MRCP) findings in a patient with right intrahepatic biliary tract obstruction due hepatic alveolar echinococcosis. A 66-year-old female patient who was diagnosed as liver alveolar hydatid cyst at the external university hospital in her anamnesis presented for evaluation of right upper-quadrant abdominal pain. MRI and MRCP were taken to patient. Lesion with hyper-intense and iso-intense components were observed in T2A images with a diameter of approximately 70x65 mm, length of 76 mm, heterogeneous intensities, no definite boundaries in liver segment 6-7 on MRI and MRCP. Continuation of right intrahepatic bile ducts was not observed due secondary to pressure of lesion. The lumen was slightly prominent in the traceable segment of approximately 7 mm. In lesion’s peripheral segments, intrahepatic bile ducts were dilated in segment 6-7 due secondary pressure of lesion. The intrahepatic main bile ducts were normally wide on the left. The diameter of the choledochus was measured approximately 9 mm at its most prominent location and is normally expanded. The gallbladder was hydropic and had a transverse diameter of approximately 48 mm. There was no calculi or matter occupying the lumen. Alveolar echinococcosis lesions mimic slow-growing tumors of the liver parenchyma that tend to infiltrate adjacent structures, especially the portal hilum, hepatic veins, inferior vena cava, and biliary system, and spread to other organs by means of hematogenous dissemination. These lesions may be misdiagnosed as malignant neoplasms if the diagnosis is based on clinical features and imaging findings of local invasion and regional or distant metastases, without serologic testing. If left untreated, alveolar echinococcosis is eventually fatal. Effective treatment options include benzimidazole therapy and surgical resection or liver transplantation.